PENGARUH KOMPETENSI KEPRIBADIAN DAN KOMPETENSI SOSIAL TERHADAP SEMANGAT KERJA DAN PROFESIONALISME GURU SMK NEGERI 2 BOJONEGORO - Nomi Wijayanti; Soenarmi Soenarmi; Nugroho Mardi W (Prodi Magister Manajemen Universitas Wijaya Putra, 2018)
This research is to know the influence of competence of personality and social competence to teacher work spirit in SMK Negeri 2 Bojonegoro. This research also wants to know the influence of work spirit toward professionalism of teacher in SMK Negeri 2 Bojonegoro; and to know the direct influence of personal competence and social competence on teacher professionalism in SMK Negeri 2 Bojonegoro. Population in this research is teacher of SMK Negeri 2 Bojonegoro which amount to 89 teachers. The sampling technique used in this study used sampling census, i.e all teachers (population) became the research sample. However, principal and researcher were not included as a sample to maintain the objectivity of the research results. The number of samples in this study were 89 teachers, hereinafter referred to as respondents. Data processing is done by path analysis, positioning the intervening variable as a liaison between the independent variable and the dependent variable. The results of personality competence research have an influence on teacher work spirit in SMK Negeri 2 Bojonegoro. Social competence does not affect the morale of teachers in SMK Negeri 2 Bojonegoro. The spirit of work and competence of the personality affect the professionalism of teachers in SMK Negeri 2 Bojonegoro. Social competence does not affect the professionalism of teachers in SMK Negeri 2 Bojonegoro. Keywords: personality competency, social competence, working spirit, teacher professionalism